Unifikasi Bacaan Al-Qur’an: Analisis Historis terhadap Kebijakan Mushaf Usmani dan Implikasinya bagi Pluralitas Qira’at - Nurul Istianah Ruddin; Halimah Basri; Aisyah Arsyad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study historically analyzes the policy of unifying the recitation of the Qur'an through the Mushaf Usmani, which became the global standard in the Islamic world. Focusing on the historical context of the era of Caliph Uthman bin Affan, this study explores how this policy aimed to maintain the unity of Muslims, but had implications for the standardization of qira'at authority. Through historical analysis and literature review, this article finds that this unification, while effective in preventing division, marginalized other qira'at, such as those known as qira'ah sab'ah. The implications include contemporary debates on the diversity of readings and efforts to revitalize plurality in Islamic education. The results of this study show that the policy of unifying the Usmani mushaf aimed to maintain the unity of the ummah by limiting the authority of Qur'anic readings, so that the recognized plurality of readings no longer included all early variations, but only qira'at that met certain legitimacy criteria.